Cost-Effectiveness of Contraceptive Use in Indonesia after the Implementation of the National Health Insurance System - Auliya A. Suwantika; Neily Zakiyah; Irma M. Puspitasari; Rizky Abdulah (Journal of Pregnancy)
Since 2014, Indonesia has initiated to implement a national health insurance system, which included both of short- (SARC) and long-acting reversible contraceptive (LARC) into the benefit package. The aim of this study was to analyze the cost-effectiveness of contraceptive use in Indonesia after the implementation of the national health insurance in 2014-2017. A decision tree model was developed to analyze the cost-effectiveness of contraceptive use in Indonesia in 2014-2017 by comparing two strategies of pregnancy prevention: contraceptive and non-contraceptive. For contraceptive strategy, we took into account SARC and LARC. In a comparison with non-contraceptive, we calculated that the incremental cost-effectiveness ratio (ICER) of SARC would be $5.18, $4.80 and $3.76 per pregnancy averted for injection, condom, and pill, respectively. For LARC, we calculated that the ICER would be $1.67 and $0.84 for implant and intrauterine device (IUD), respectively, compared with non-contraceptive. In general, the cost-effectiveness value of LARC ($1.25) was much better than SARC ($4.58). The cost of contraceptive was considered to be the most influential parameter affecting both the ICER of SARC and LARC. In conclusion, the use of LARC in Indonesia was considered to be more cost-effective than SARC since the implementation of national health insurance system. In particular, IUD yielded the greatest cost-effectiveness value, compared with other methods.